PENGEMBANGAN MEDIA EVALUASI BERBASIS GAMIFIKASI DENGAN BERBANTU WEBSITE EDUCAPLAY UNTUK MENINGKATKAN MINAT BELAJAR SISWA IPAS KELAS V SD - Nur Fatma, Intan; Fitrah Dwi, Dara; Risnawati; Sukmawarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted because students’ level of interest in participating in the assessment process during learning is relatively low. Traditional assessment methods with little variation cause students to quickly become bored. The objective of this study is to develop an evaluation medium based on gamification through the Educaplay website, while also evaluating the feasibility and effectiveness of this medium in increasing students’ interest in learning the IPAS subject for fifth-grade elementary school students. The method applied is Research and Development (R&D) using the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The participants in this study were fifth-grade students from SD Negeri 067259 in Medan. Data collection was conducted through observation, interviews, and questionnaires covering expert validation, teacher feedback, student responses, and students’ level of interest in learning. The research findings indicate that the media received a validation score of 94% from subject matter experts and 91% from evaluation experts, which falls into the “highly acceptable” category. Feedback from teachers reached 95% and student responses were 88%, which are also classified as highly acceptable. Additionally, the results of the pretest and posttest showed an increase in student learning interest from 45% to 90%. Thus, gamification-based assessment media using Educaplay is considered effective in increasing student learning interest and can serve as an innovative alternative for learning assessment at the elementary school level.